Clinical features of depression in men with testosterone deficiency - Yu. Yu. Osadshiy; M. N. Kryuchkova; A. A. Sidorov; A. Ya. Perekhov (Медицинский вестник Юга России, 2025)
Objective: to study the clinical features of depression in men with low testosterone levels. Materials and methods: the study included 140 males aged 18 to 65 years diagnosed with recurrent depressive disorder (F33) and a depressive episode (F32) according to ICD-10. The main group consisted of men with depression comorbid with testosterone deficiency (n = 90). The control group included men with depression and normal testosterone levels (n = 50). Results: symptoms of depression in men with testosterone deficiency were less severe and led to less functional disturbance. There were some clinical differences in symptoms and syndromes such as sexual function, sleep, irritability, alcohol consumption, severe and functionality, main syndrome etc. For the main group was more typical mono-episode with manifestation at a later age while for the control group recurrent episodes manifesting at an earlier age were more typical. Conclusions: depression in men with testosterone deficiency has a number of differences that must be taken into account when diagnosing and choosing treatment tactics.